Estudo de barreira acústica no controle de ruído em um câmpus universitário - Amarilla, Rosemara Santos Deniz (2019)
Urbanization is one of the major global trends of the 21st century, becoming a great challenge to evaluate and manage environmental noise, because there is a concern with the reduction of noise pollution in cities and their buildings, due to the well-being and health of the population. Based on this contexto, the present thesis aims to study simple acoustic barrier of concrete blocks by means of computational simulation. Therefore, a new sound absorption coefficient was introduced in the SoundPlan software library which characterizes concrete blocks of construction and demolition waste (CDW), representing a sustainable solution for waste problems and for the control of traffic noise in a university campus in the city of Curitiba, Paraná, Brazil. The research has a dual environmental benefit, on the one hand, reducing the impact of noise pollution levels and, on the other hand, recycling by-product of construction and demolition (CDW), material used in the simulation of the acoustic barrier. In this study used the field research technique, exploratory and experimental study. The data of the sound impact that reaches the academic area were collected in loco and calculated in the software of predic tion, noting that the sound levels were above the limit recommended by NBR 10151: 2000 and by Municipal Law nº. 10625: 2002, mainly, the receiving points close to the vehicular traffic lanes. Consequently, the results of the simulations, after insertion of the acoustic barrier, showed an average noise attenuation of 12 dB around the Campus. Concludes that besides sound attenuation, the blocks produced with RCD become a practice for sustainability.